Botulinum toxin in treating Hailey‐Hailey disease: A systematic review. (5th February 2021) - Zhang, Hanlin; Tang, Keyun; Wang, Yuchen; Fang, Rouyu; Sun, Qiuning
Abstract: Background: Hailey‐Hailey disease is a rare disorder characterized by recurrent painful blistering, erosions, maceration in the intertriginous regions. Botulinum toxin has been used in the treatment of Hailey‐Hailey disease. Aims: This study aimed to examine all published articles on botulinum toxin in the treatment of Hailey‐Hailey disease, and to evaluate its efficacy and safety. Methods: PubMed, Embase, Cochrane Library, and Web of Science were used to identify eligible articles on August 8, 2020. The searching strategy was "(Hailey Hailey or Hailey‐Hailey or pemphigus) and botulinum." Results: Sixteen articles including 38 patients described the use of botulinum toxin in treating Hailey‐Hailey disease. Only one case had no response, while the other patients all had partial or complete remission. No side effects were reported. Nine articles including 10 patients mainly described other treatment options, and the patients were only treated with botulinum toxin previously. Their responses to botulinum toxin were limited: one was mild improvement, one was partial response, and the other eight failed. Conclusion: Botulinum toxin is not almighty, but a promising alternative option. We recommend botulinum toxin as an adjuvant or supplemental treatment modality for severe and recalcitrant Hailey‐Hailey disease. Larger studies are warranted to confirm its efficacy, safety, long‐term effects, and cost performance.